Political Stability And The Well-Being Of First Nations In Saskatchewan: Implications for the Proposed First Nations Elections Act - Natcher, David C.; Olfert, Rose; Boaitey, Albert; Allen, Tom (Journal of Aboriginal Economic Development, 2013)
This paper provides an empirical analysis of the relationship between the political stability of First Nations in Saskatchewan and a number of measures of social and economic well-being. Our results show that among First Nations in Saskatchewan the average term of elected leadership is 4.5 years. Simple descriptive statistics support the basic hypothesis that more stability, represented as less frequent changes in elected Chiefs, is associated with better socio-economic outcomes for First Nation communities. Our findings also show evidence that there are limits to how much more socio-economic gains can be achieved by increasing political stability of First Nation governments. At some point the positive contribution of greater stability to socio-economic outcomes decreases, such that it may eventually reduce, rather than improve positive socio-economic outcomes. With this paper we hope to inform the current debate of the merits or risks associated with any future changes in First Nation elections and their resulting systems of governance.